Perbedaan Laju Alir Partikel Pakan Berbagai Pakan Serat dalam Sistem Rumen Sapi - Yunasri Usman (Jurnal Agripet, 2015)
(The differences of passage rate of feed particles from various crude fiber feed in dairy cattle rumen)ABSTRACT. The differences of passage rate particles is considerably influenced by different feed consumption relating to the nature of feed, types of animals, and physiological status of animals. The purpose of this experiments was to measure differences of passage rate feed particles at various crude fiber feed in cows rumen. This experiment used two cows of fistulated crossed breed Frisian Holland (PFH), non-productive with the age of 4-5 years. Feed observed in this experiments were peanut straw, corn straw and sugar cane straw and fed as single feed. Method applied to measure passage rate was chrome mordanse/chrome and NDF as marker introduced through fistulated rumen. All data were analyzed by using regression. The value of passage rate (Kp) was about 3,7% per hour for peanut straw, and 2,5% per hour for corn straw and sugar cane straw. Kp value of peanut straw was higher than that of corn straw and sugar cane straw. The highest value of Kp for peanut srtaw was due to better quality of peanut straw compared to corn straw and sugar cane straw in which peanut straw contained high level of protein and low level of Neutral Detergent Fiber (NDF). The differences of chemical composition of crude fiber feed from peanut straw with high level of protein and low level of NDF compared to corn straw and sugar cane straw resulted in degradation of feed by microbial rumen was higher, low rumination. It caused higher passage rate of feed.